First report of root-knot nematode, Meloidogyne incognita, infecting hops, Humulus lupulus, in São Paulo, Brazil - Gonsaga, R. F. [UNESP]; Souza Pollo, A. [UNESP]; Nascimento, D. D. [UNESP]; Ferreira, R. J. [UNESP]; Braz, L. T. [UNESP]; Soares, P. L.M. [UNESP] (De Gruyter, 2021)
In 2019, during a nematologic survey in Jaboticabal, Brazil, root-knot nematode Meloidogyne incognita parasitizing hops (Humulus lupulus) was identified with based on morphological characters of adults, esterase phenotypes (n=16), and molecular analysis. Modified Koch's postulates was carried out and after 90 days, the average total population recovered had different stages of development, with a reproductive factor (RF) of 4.81. This is the first report of H. lupulus as a host of M. incognita in the state of São Paulo and in Brazil.
Keywords: Detection; Diagnosis; First occurrence